Penyuluhan Koperasi Petani Jeruk di Nagari Koto Tinggi Kecamatan Gunung Omeh Kabupaten Limapuluh Kota - Weriantoni Weriantoni; Erizal Nazaruddin; Lukman Lukman; Amra Ausri; Khadijah Khadijah; Nurul Fadhilah; Rahmat Fadhilah; Elva Yulianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
This service aims to introduce the concept and utilization of cooperatives to citrus farmers in Gunung Omeh District, Limapuluh Kota Regency. The method used was the lecture method (counseling) and training. There were many farmers who do not know about cooperatives, cooperative objectives, cooperative benefits and how the cooperative formation process and willing to form a cooperative formation committee. It was hoped that the government can help the farmers to establish an cooperative system.